2020
DOI: 10.4269/ajtmh.19-0934
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence of Helicobacter pylori/CagA Antibodies in Guatemalan Gastric Cancer Patients: Association of Seropositivity with Increased Plasma Levels of Pepsinogens but not Soluble Urokinase Plasminogen Activator Receptor

Abstract: Infection by Helicobacter pylori is a major risk factor for gastric cancer (GC), the second leading cause of cancer-related death worldwide. Although biomarkers such as pepsinogens (PGs) and soluble urokinase plasminogen activator receptor (suPAR) may have diagnostic and/or prognostic value in patients with GC, their levels may be affected by H. pylori infection. The aim of this study was to investigate the association of the presence of antibodies to H. pylori and cytotoxin-associated gene A (CagA) with plasm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 45 publications
0
3
0
2
Order By: Relevance
“…Second, the absence of anti-CagA antibodies in such patients may be due to sequence variation in CagA resulting in different epitopes [ 29 ]. It could also be due to the low level of antibodies produced against the antigen used in the ELISA kit [ 30 ]. Generally, the inability to differentiate between current and past infection may interpret the low accuracy of serological tests [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Second, the absence of anti-CagA antibodies in such patients may be due to sequence variation in CagA resulting in different epitopes [ 29 ]. It could also be due to the low level of antibodies produced against the antigen used in the ELISA kit [ 30 ]. Generally, the inability to differentiate between current and past infection may interpret the low accuracy of serological tests [ 4 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, this marker may be considered a risk factor for the development of gastric cancer. 31,32 The current study showed that donors with blood group O/Rhþ had higher seroprevalence of anti-CagA IgG marker than donors of other blood groups. However, no significant associations were detected between anti-CagA IgG seropositivity and any blood groups.…”
Section: Discussionmentioning
confidence: 57%
“…Focusing on the relationship between PgII and CagA status, in keeping with results previously obtained by Broutet et al, 13 Okuda et al recently confirmed that serum PgII levels were significantly higher in CagA‐seropositive infection (PgII levels: 9.0 µg/L in CagA‐negative individuals versus 15.3 µg/L in CagA‐positive ones; p = 0.001). This difference retained a borderline significance even when cancer patients were considered 25 …”
Section: Resultsmentioning
confidence: 91%